Opioid use after cesarean: a cohort study comparing combined versus separate oxycodone and acetaminophen regimens. (12th December 2022) - Birchall, Courtney L.; Maines, Jaimie L.; Kunselman, Allen R.; Stetter, Christy M.; Pauli, Jaimey M.
Abstract: Objective: To determine whether an inpatient post-cesarean analgesic regimen which separated oxycodone and acetaminophen resulted in less inpatient opioid use, when compared to a regimen using combination medications containing both acetaminophen and oxycodone in a cohort including patients of all gestational ages, acuity levels, and modes of operative anesthesia. Methods: This is a retrospective cohort study which was conducted at a single tertiary care center Labor and Delivery unit. Data were collected via retrospective chart review, and a total of 170 records were examined with a final N = 150. Inclusion criteria were all patients over the age of 18, and >23.0 weeks gestational age, who had a singleton or twin cesarean delivery regardless of their mode of operative anesthesia and whether or not they received intrathecal opioid at time of delivery. Exclusion criteria were pregnancies of higher-level multiples (triplets or greater), prolonged intensive care unit (ICU) stay, and patients who received both combination oxycodone-acetaminophen and separately administered oxycodone. For analysis patients were classified into two groups: the "Combined Medication" group representing patients who received combination oxycodone-acetaminophen medication only ( n = 83) and the "Separate Medication" group representing patients who received oxycodone and acetaminophen separately ( n = 67). Differences between the groups with respect to opioid use and acetaminophen use were assessed. Results: The primary outcome was inpatient opioid medication use per 12-h period in intravenous morphine mg equivalents (MME). Patients received an average of 4.6 ± 3.5 MME IV morphine per 12 h in the Separate Medication group and 5.7 ± 3.7 MME IV morphine per 12 h in the Combined Medication group. When controlled for several covariates, the Separate Medication group took significantly fewer MME per 12-h period (mean difference = −1.2, 95% CI: (−2.3, −0.1), p = .04). There was no appreciable difference in acetaminophen utilization between groups. Conclusions: An analgesic regimen where oxycodone is ordered separately from acetaminophen is associated with reduced inpatient opioid medication use in patients of all gestational ages, acuity levels, and modes of operative anesthesia.